Microwave assisted fast and clean conversion of mesylate to azide: synthesis of (1S,2R/1R,2S)-1-azido-2-carbocyclic amines as immediate precursors to versatile 1,2-cis-diamines - Govindaraju, T. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2006)
An efficient and rapid conversion of mesylate to azide under microwave irradiation has been carried out. It proceeds through inversion of configuration from chiral mesylates to provide optically pure cis-azides, immediate precursors of vicinal-cis-1,2-diamines. These diamines can serve as metal ligands in asymmetric catalysis and their derivatives can be employed as medicinal agents.
Keywords: asymmetric catalysis; Azide; diamines; medicinal agent; mesylate; microwave irradiation